Novel bleeding risk score for patients with atrial fibrillation on oral anticoagulants, including direct oral anticoagulants. (24th February 2021) - Adam, Luise; Feller, Martin; Syrogiannouli, Lamprini; Del‐Giovane, Cinzia; Donzé, Jacques; Baumgartner, Christine; Segna, Daniel; Floriani, Carmen; Roten, Laurent; Fischer, Urs; Aeschbacher, Stefanie; Moschovitis, Giorgio; et al.
Abstract: Objective: Balancing bleeding risk and stroke risk in patients with atrial fibrillation (AF) is a common challenge. Though several bleeding risk scores exist, most have not included patients on direct oral anticoagulants (DOACs). We aimed at developing a novel bleeding risk score for patients with AF on oral anticoagulants (OAC) including both vitamin K antagonists (VKA) and DOACs. Methods: We included patients with AF on OACs from a prospective multicenter cohort study in Switzerland (SWISS‐AF). The outcome was time to first bleeding. Bleeding events were defined as major or clinically relevant non‐major bleeding. We used backward elimination to identify bleeding risk variables. We derived the score using a point score system based on the β‐coefficients from the multivariable model. We used the Brier score for model calibration (<0.25 indicating good calibration), and Harrel's c‐statistics for model discrimination. Results: We included 2147 patients with AF on OAC (72.5% male, mean age 73.4 ± 8.2 years), of whom 1209 (56.3%) took DOACs. After a follow‐up of 4.4 years, a total of 255 (11.9%) bleeding events occurred. After backward elimination, age > 75 years, history of cancer, prior major hemorrhage, and arterial hypertension remained in the final prediction model. The Brier score was 0.23 (95% confidence interval [CI] 0.19–0.27), the c‐statistic at 12 months was 0.71 (95% CI 0.63–0.80). Conclusion: In this prospective cohort study of AF patients and predominantly DOAC users, we successfully derived a bleeding risk prediction model with good calibration and discrimination.